A novel nonsense variant in REEP6 is involved in a sporadic rod‐cone dystrophy case. Issue 3 (27th February 2018) - Méjécase, C.; Mohand‐Saïd, S.; El Shamieh, S.; Antonio, A.; Condroyer, C.; Blanchard, S.; Letexier, M.; Saraiva, J.‐P.; Sahel, J.‐A.; Audo, I.; Zeitz, C.
Abstract : Rod‐cone dystrophy (RCD), also called retinitis pigmentosa, is the most common form of progressive inherited retinal disorders secondary to photoreceptor degeneration. It is a genetically heterogeneous disease characterized by night blindness, followed by visual field constriction and, in most severe cases, total blindness. The aim of our study was to identify the underlying gene defect leading to severe RCD in a 60‐year‐old woman. The patient's DNA was investigated by targeted next generation sequencing followed by whole exome sequencing. A novel nonsense variant, c.267G>A p.(Trp89*), was identified at a homozygous state in the proband in REEP6 gene, recently reported mutated in 7 unrelated families with RCD. Further functional studies will help to understand the physiopathology associated with REEP6 mutations that may be linked to a protein trafficking defect. Abstract : We report here a novel homozygous nonsense variant c.267G>A p.(Trp89*) in REEP6 in a patient with rod‐cone dystrophy (RCD) originating from a North Africa consanguineous couple. This third report of REEP6 variants associated with RCD provides further evidence that REEP6 must be investigated in RCD cases.